2010
DOI: 10.1080/15257770.2010.496279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chloride, Bromide, and Iodide Upon Decomposition of Nucleosides Induced by Ultrasound in Neutral Solution

Abstract: When the ultrasound of 42 kHz was irradiated on a neutral mixture of 2'-deoxycytidine, 2'-deoxyguanosine, 2'-deoxythymidine, and 2'-deoxyadenosine, concentrations of all the nucleosides decreased. Addition of NaCl to the system had no effect. NaBr suppressed the reactions for all the nucleosides, but the efficiency of 2'-deoxyguanosine was low. NaI suppressed the reactions for all the nucleosides more effectively. A comparison with the results of the effects of halides on the reaction of nucleosides by a Fento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Among the 45 compounds, additives that strongly suppressed the consumption of nucleosides were ascorbic acid and its derivatives, Trolox, thiols and its derivatives, tryptophan, tyrosine, catecholamines, trans - p -coumaric acid, trans -2-hexenal, trans -2-hexen-1-ol, donepezil, penicillin G, metformin, NaBr, NaI, and NaHSO 3 . Ascorbic acid is an effective antioxidant and a radical scavenger.‍ ( 29 , 30 ) Various ascorbic acid derivatives are synthesized as ingredients of cosmetics for antioxidant protection against UV-induced photodamage.‍ ( 31 33 ) Trolox acts as a multiple free radical scavenger.‍ ( 34 ) Thiols are important antioxidants in cells and body fluids.‍ ( 35 ) In addition to thiols, glutathione disulfide, a disulfide, and methionine, a thioether, also reduce oxidative DNA damage.‍ ( 36 , 37 ) Although tryptophan is not a good antioxidant, its oxidative metabolites scavenge peroxyl radicals with high efficiency.‍ ( 38 ) Tyrosine, a nomophenolic compound, shows antioxidant and antiradical activities.‍ ( 39 ) Catecholamines, diphenolic compounds, are scavenger of radicals.‍ ( 40 , 41 ) trans - p -Coumaric acid, a monophenolic acid, is ubiquitously distributed in fruits and vegetables and shows antioxidant and radical scavenging activities.‍ ( 42 ) trans -2-Hexenal, an α , β -unsaturated aldehyde, and trans -2-hexen-1-ol, an α , β -unsaturated alcohol, are major volatile compounds in green leaves and olive oil.‍ ( 43 ) Although trans -2-hexenal is mutagenic due to generating a cyclic adduct with dG, it acts as a hydroxyl radical scavenger.‍ ( 44 , 45 ) It has been reported that cis -2-hexen-1-ol, a cis isomer of trans -2-hexen-1-ol, shows radical scavenging activity greater than that of trans -2-hexenal.‍ ( 46 ) Donepezil can act as an antioxidant and a radical scavenger.‍ ( 47 ) Penicillin G, an antibiotic, can act as a scavenger of radicals, since it has a cyclic thioether moiety, which is acceptable for free radicals.‍ ( 48 , 49 ) Metformin, an anti­hyperglycemic drug for type 2 diabetes, shows radical scavenging effects.‍ ( 50 ) The bromide ion (Br‍ − ) and iodide ion (I‍ − ) show scavenging effects for ‍ • OH.‍ ( 51 ) The bisulfite ion (HSO 3 ‍ − ), a reducing reagent, is widely added to tap water and food because of its antioxidant, antibacterial, and bleaching effects.‍ ( 52 ) All of t...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 45 compounds, additives that strongly suppressed the consumption of nucleosides were ascorbic acid and its derivatives, Trolox, thiols and its derivatives, tryptophan, tyrosine, catecholamines, trans - p -coumaric acid, trans -2-hexenal, trans -2-hexen-1-ol, donepezil, penicillin G, metformin, NaBr, NaI, and NaHSO 3 . Ascorbic acid is an effective antioxidant and a radical scavenger.‍ ( 29 , 30 ) Various ascorbic acid derivatives are synthesized as ingredients of cosmetics for antioxidant protection against UV-induced photodamage.‍ ( 31 33 ) Trolox acts as a multiple free radical scavenger.‍ ( 34 ) Thiols are important antioxidants in cells and body fluids.‍ ( 35 ) In addition to thiols, glutathione disulfide, a disulfide, and methionine, a thioether, also reduce oxidative DNA damage.‍ ( 36 , 37 ) Although tryptophan is not a good antioxidant, its oxidative metabolites scavenge peroxyl radicals with high efficiency.‍ ( 38 ) Tyrosine, a nomophenolic compound, shows antioxidant and antiradical activities.‍ ( 39 ) Catecholamines, diphenolic compounds, are scavenger of radicals.‍ ( 40 , 41 ) trans - p -Coumaric acid, a monophenolic acid, is ubiquitously distributed in fruits and vegetables and shows antioxidant and radical scavenging activities.‍ ( 42 ) trans -2-Hexenal, an α , β -unsaturated aldehyde, and trans -2-hexen-1-ol, an α , β -unsaturated alcohol, are major volatile compounds in green leaves and olive oil.‍ ( 43 ) Although trans -2-hexenal is mutagenic due to generating a cyclic adduct with dG, it acts as a hydroxyl radical scavenger.‍ ( 44 , 45 ) It has been reported that cis -2-hexen-1-ol, a cis isomer of trans -2-hexen-1-ol, shows radical scavenging activity greater than that of trans -2-hexenal.‍ ( 46 ) Donepezil can act as an antioxidant and a radical scavenger.‍ ( 47 ) Penicillin G, an antibiotic, can act as a scavenger of radicals, since it has a cyclic thioether moiety, which is acceptable for free radicals.‍ ( 48 , 49 ) Metformin, an anti­hyperglycemic drug for type 2 diabetes, shows radical scavenging effects.‍ ( 50 ) The bromide ion (Br‍ − ) and iodide ion (I‍ − ) show scavenging effects for ‍ • OH.‍ ( 51 ) The bisulfite ion (HSO 3 ‍ − ), a reducing reagent, is widely added to tap water and food because of its antioxidant, antibacterial, and bleaching effects.‍ ( 52 ) All of t...…”
Section: Resultsmentioning
confidence: 99%
“…(50) The bromide ion (Br − ) and iodide ion (I − ) show scavenging effects for • OH. (51) The bisulfite ion (HSO 3 − ), a A mixed solution of 100 μM dC, dG, dT, and dA in 100 mM potassium phosphate buffer at pH 7.4 in the presence of 400 μM uric acid and 5 mM additives was irradiated with UV light through a 300-nm longpass filter at a temperature of 37°C for 20 min. ND denotes not determined due to overlapping peaks on the PR-HPLC chromatogram.…”
Section: Resultsmentioning
confidence: 99%
“…Suzuki et al (11) studied the effects of chloride, bromide, and iodide upon the decomposition of all four deoxynucleosides in solution induced by 42-kHz ultrasound in neutral solution. Their starting mixture was 100 μ m in each of the four deoxynucleosides in 100 m m phosphate buffer, pH 7.4.…”
Section: Dna Damage Involving 2 ′ -Deoxyadenosinementioning
confidence: 99%
“…These data were then rationalized in terms of standard oxidation potentials of the deoxynucleosides and those of the halides. Essentially, the hydroxyl radicals produced reacted with the halide anions giving halide radicals, which in turn resulted in dihalide radical anions (11) . Addition of bromide through certain food additives can increase its plasma concentration to check the nucleoside decomposition, but not completely.…”
Section: Dna Damage Involving 2 ′ -Deoxyadenosinementioning
confidence: 99%